“Shadow of a Doubt”—The Pathogenic Role of Endometrial Defects in Endometriosis Development and Endometriosis-Associated Infertility: Robust Demonstration of Clinical Relevance Is Still Urgently Needed - Paola Viganò; Maíra Casalechi; Paolo Vercellini; Edgardo Somigliana (Biomolecules, 2023)
Endometriosis is an estrogen-dependent chronic inflammatory disease characterized by the presence of endometrial glands and stroma associated with fibrosis outside the uterine cavity [...]